Why do we not have a cure for rheumatoid arthritis? - El-Gabalawy, Hani D (BioMed Central, 2002)
CHAPTER SUMMARY: There are currently unprecedented opportunities to treat rheumatoid arthritis using well-designed, highly effective, targeted therapies. This will result in a substantial improvement in the outcome of this disorder for most affected individuals, if they can afford these therapies. Yet our lack of understanding of the basic mechanisms that initiate and sustain this disease remains a major obstacle in the search for a definitive cure. It is possible, if not likely, that our best approach will be to identify individuals at risk and devise reliable, safe methods of preventing the disease before it occurs. The means to do this are currently unknown but should serve as a major focus of research.